Three-Species Lotka-Volterra Food Chain Model with Fear Effect and Hunting Cooperation - Allawi Dakhil, Rehab; Jasim Majeed, Salam (University of Thi-Qar Journal, 2023)
From an ecological standpoint, the dynamics of the food chain model under the fear that is thus placed on the predator population and the inuence of cooperative hunting among them are quite significant. In the current paper, we use the food chain Lotka-Volterra predator-prey model to examine the effects of hunting cooperation among middle predators and top-predator-induced fear in the middle predator population. The system has four points of equilibrium. The model’s dynamical characteristics are studied. It has been discovered that dynamical behavior is quite sensitive to parameter values and displays a range of dynamics without degenerating into chaos and that the presence of cooperation and fear signicantly affects the stability of the dynamics of the system. Computer simulations have been used to illustrate the theoretical results